Field-evaluation of DRAINMOD-S for predicting soil and drainage water salinity under semi-arid conditions in Turkey - Kale, S. (Spanish Journal of Agricultural Research, 2011)
<span style="font-size: 9pt; line-height: 115%; font-family: ’Verdana’,’sans-serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;" lang="EN-US">The aim of this study was to determine the reliability of DRAINMOD-S for simulating water management in irrigated land and to simulate drainage system design criteria to ensure high crop yields for the western part of the Central Kızılırmak Basin in Turkey. The model was tested under arid conditions using field data for winter wheat and corn. Daily water-table depth, drain outflows and drainage water salinity were monitored throughout the growing season. Soil salinities were measured to a depth of 1.00 m from the soil surface. The reliability of the model was evaluated by comparing measured and predicted values of the daily ground water table depth, drain outflows, drainage water and soil salinity during each season, and relative crop yield. Good agreement was found between the measured and predicted values. Absolute deviation was 5.68 cm for water table depth, 10.13 mm for drain outflows, 0.66 dS m–1 for drainage water salinity, and ranged from 0.51 to 0.96 dS m–1 for soil salinity. The corresponding coefficients of efficiency (<span style="font-size: 9pt; line-height: 115%; font-family: ’Verdana’,’sans-serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;" lang="EN-US">E<span style="font-size: 9pt; line-height: 115%; font-family: ’Verdana’,’sans-serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;" lang="EN-US">) were between 0.48 and 0.95. The results also showed that Drainmod -S can be recommended as a useful tool for design and evaluation of irrigation and drainage systems in salt-affected soils under arid and semi-arid climates.